(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Cancer-related malnutrition has an adverse effect on morbidity, mortality, and quality of life of an individual. Nutrition Impact Symptom (NIS) commonly occurs in cancer patients commencing chemotherapy and may initiate malnutrition. However, there is less knowledge regarding NIS of cancer patients in Indonesia. Therefore, this study aims to identify the association between NIS and malnutrition. A cross-sectional study was conducted at Kariadi General Hospital. Adult patients who had chemotherapy from March-April 2022 were included. Malnutrition incidences were assessed by Patient-Generated Subjective Global Assessment (PG-SGA), and NIS was evaluated by box 3 (symptoms) of PG-SGA. Out of 267 patients, 58.1 percent were female, 18.7 percent were aged over 60 years, and 85 percent were categorized as malnutrition based on PG-SGA. After a multivariate analysis, NIS having the most association with malnutrition were pain (OR = 11.78, 95%CI = 1.47- 94.2, p = 0.02), nausea (OR = 5.75, 95%CI = 2.14 -15.4, p = 0.001) and anorexia (OR = 3.85, 95%CI = 1.32 -11.2, p = 0.013). Patients experiencing NIS more than 2 had an association with malnutrition (p = 0.000). There was a high proportion of malnutrition and NIS in this population. Screening and assessment of NIS utilizing assessment tools should be incorporated into nutritional assessment in oncology patients on chemotherapy since NIS is associated with malnutrition. Further research on NIS and malnutrition is vital in patients with cancer during chemotherapy.